Managing Nutrition After Cytoreductive Surgery and Hyperthermic Intraperitoneal Chemotherapy (CRS-HIPEC): A Qualitative Study of Colorectal Cancer Survivors’ and Caregivers’ Experiences - Kea Turner; Amir Alishahi Tabriz; Ryan Chi-Hsuan Su; Brent J. Small; Emma Hume; Olivia Sprow; Christina Santiago; Jennifer B. Permuth; Benjamin D. Powers; Jeremiah L. Deneve; Sean P. Dineen (Journal of the Academy of Nutrition and Dietetics, 2026)

Participation in collaborative fisheries research improves the perceptions of recreational anglers towards marine protected areas - Erin M. Johnston; Grant T. Waltz; Rosamaria Kosaka; Ellie M. Brauer; Shelby L. Ziegler; Erica T. Jarvis Mason; Hunter S. Glanz; Lauren Zaragoza; Allison N. Kellum; Rachel O. Brooks; Brice X. Semmens; Christopher J. Honeyman; et al. (Frontiers in Marine Science, 2024)
Collaborative fisheries research programs engage stakeholders in data collection efforts, often with the benefit of increasing transparency about the status and management of natural resources. These programs are particularly important in marine systems, where management of recreational and commercial fisheries have historically been contentious. One such program is the California Collaborative Fisheries Research Program (CCFRP), which was designed in 2006 to engage recreational anglers in the scientific process and evaluate the efficacy of California’s network of marine protected areas. CCFRP began on the Central Coast of California and expanded statewide in 2017 to include six partner institutions in three regions: Northern, Central, and Southern California. To date, over 2,000 volunteer anglers have participated in the program, with many anglers volunteering for multiple years. However, the impacts of outreach, education, and collaborative research on those anglers at the statewide scale are currently unknown. Thus, the objective of the current study was to survey the statewide pool of volunteer anglers to assess the degree to which participation in CCFRP has influenced angler perceptions of MPAs, fisheries management, and conservation. We received 259 completed surveys out of a pool of 1,386 active anglers, equating to an 18.7% response rate. Participation in CCFRP resulted in a significant, positive impact on anglers’ attitudes towards MPAs in California across all regions. Anglers who participated in six or more CCFRP fishing trips had a more positive perception of MPAs than those who participated in fewer trips. Volunteer anglers across all regions perceived that they caught larger fishes, a higher abundance of fishes, and a greater diversity of species inside MPAs, consistent with the ecological findings of the program. These results highlight the benefits of involving community members in collaborative scientific research. Collaboration between researchers and the broader community increases transparency and trust between stakeholders, and results in greater understanding of natural resource dynamics, ultimately producing better management outcomes.

John squire and endothelial glycocalyx structure: an unfinished story - Kenton P. Arkill; C. Charles Michel; Elizabeth V. M. Rider; Elise A. Wood; Mathew O. Small; Jennifer L. E. Brown; Abigail L. Kinnaird (Journal of Muscle Research and Cell Motility, 2023)
John Squire did not only produce leading works in the muscle field, he also significantly contributed to the vascular permeability field by ultrastructural analysis of the endothelial glycocalyx. Presented here is a review of his involvement in the field by his main collaborator C.C. Michel and his last postdoctoral researcher KP Arkill. We end on a reinterpretation of his work that arguably links to our current understanding of endothelial glycocalyx structure and composition predicting 6 glycosaminoglycans fibres per syndecan core protein, only achieved in the endothelium by dimerization.

Genetic composition and conservation status of coastal cutthroat trout (Oncorhynchus clarki clarki) in the San Juan Islands, Washington - Jamie Glasgow; Jennifer D. De Groot; Maureen P. Small (Conservation Genetics, 2020)
Understanding the conservation status of native fish populations is increasingly important because they are put at risk by mounting anthropogenic pressures, including climate change. Conventional approaches to assess fish populations can be logistically challenging and cost-prohibitive. As a result, resource managers often make assumptions about the status of fish populations based on limited information. The watersheds of Washington’s San Juan Islands were considered too small to support wild salmonid populations. Many streams flow only seasonally, and all have been subjected to varying degrees of anthropogenic impacts affecting their ecological integrity. Nonetheless, we found that at least five watersheds in the archipelago support populations of coastal cutthroat trout ( Oncorhynchus clarki clarki ). To better understand the conservation status of coastal cutthroat trout populations there, we genotyped approximately fifty trout in each of three watersheds: Cascade and Doe Bay creeks on Orcas Island and Garrison Creek on San Juan Island. Results suggest that two watersheds support native populations and one supports naturalized hatchery fish. The likely native coastal cutthroat trout diversity documented in the two watersheds contributes to the overall diversity of the species, demonstrates that species’ resiliency, and provides justification for conservation measures. Effective management and conservation planning in data-limited situations requires the use of a precautionary approach. Population genetics provide a useful tool for identifying vulnerable fish populations and understanding their relationships with other conspecific populations. This information can inform restoration goals and help identify and prioritize restoration and protection measures.

Comparing inferences derived from microsatellite and RADseq datasets: a case study involving threatened bull trout - Justin Bohling; Maureen Small; Jennifer Von Bargen; Amelia Louden; Patrick DeHaan (Conservation Genetics, 2019)

A global database of nitrogen and phosphorus excretion rates of aquatic animals - Michael J. Vanni; Peter B. McIntyre; Dennis Allen; Diane L. Arnott; Jonathan P. Benstead; David J. Berg; Åge Brabrand; Sébastien Brosse; Paul A. Bukaveckas; Adriano Caliman; Krista A. Capps; Luciana S. Carneiro; et al. (Ecology, 2017)
Animals can be important in modulating ecosystem‐level nutrient cycling, although their importance varies greatly among species and ecosystems. Nutrient cycling rates of individual animals represent valuable data for testing the predictions of important frameworks such as the Metabolic Theory of Ecology ( MTE ) and ecological stoichiometry ( ES ). They also represent an important set of functional traits that may reflect both environmental and phylogenetic influences. Over the past two decades, studies of animal‐mediated nutrient cycling have increased dramatically, especially in aquatic ecosystems. Here we present a global compilation of aquatic animal nutrient excretion rates. The dataset includes 10,534 observations from freshwater and marine animals of N and/or P excretion rates. These observations represent 491 species, including most aquatic phyla. Coverage varies greatly among phyla and other taxonomic levels. The dataset includes information on animal body size, ambient temperature, taxonomic affiliations, and animal body N:P. This data set was used to test predictions of MTE and ES , as described in Vanni and McIntyre (2016; Ecology DOI : 10.1002/ecy.1582 ).

Effects of experimental rainfall manipulations on Chihuahuan Desert grassland and shrubland plant communities - Selene Báez; Scott L. Collins; William T. Pockman; Jennifer E. Johnson; Eric E. Small (Oecologia, 2013)

A Satellite Model of Forest Flammability - Marc K. Steininger; Karyn Tabor; Jennifer Small; Carlos Pinto; Johan Soliz; Ezequiel Chavez (Environmental Management, 2013)

Local landscape composition and configuration around North American Breeding Bird Survey routes - Michael F. Small; Joseph A. Veech; Jennifer L. R. Jensen (Ecology, 2012)
Large‐scale monitoring of avian species is often conducted by observers driving rural roads and highways. Surveys along roads allow for easy and reliable access over time and the ability to survey large geographic areas in a relatively short period of time. However, if the landscape directly adjacent to these roadside transects is not representative of the greater landscape inhabited by the bird species, then estimates of abundance along the route may not be accurate for the greater landscape. Moreover, inferences regarding abundance, distribution, population trend, and habitat use in the greater landscape may not be valid. Using land cover data from the National Land Cover Database (NLCD), we recently conducted an assessment that revealed a satisfactorily high level of similarity in land cover composition between landscapes immediately adjacent to North American Breeding Bird Survey (BBS) routes (Buffer distance of 0.4 km on either side of route) and the larger landscapes (buffer distance of 10 km) in which they are embedded. Thus, local representativeness was high, as was regional representativeness (a comparison of similarity between combined local landscapes and a larger region containing the routes). Motivated by this positive outcome, we now provide a data set of land cover composition in six different‐sized landscapes and land configuration in four different‐sized landscapes surrounding each of 3980 BBS routes. We used a geographic information system (GIS) to produce 30 × 30 m raster maps of NLCD 2006 land cover types for each route in each of 30 Bird Conservation Regions. For each BBS route, the data set consists of pixel counts for each of 16 land cover types. These pixel counts are suitable for conversion into proportions for comparison of landscapes of different sizes. Additionally, we provide three measures of landscape configuration for each BBS route. The data set will be useful to researchers analyzing BBS bird data as it represents the first time that a vast majority of BBS routes have been individually linked to a land cover database.

Eyespan reflects reproductive quality in wild stalk-eyed flies - Samuel Cotton; Jennifer Small; Rosli Hashim; Andrew Pomiankowski (Evolutionary Ecology, 2010)

Remotely Sensed Interannual Variations and Trends in Terrestrial Net Primary Productivity 1981?2000 - Mingkui Cao; Stephen D. Prince; Jennifer Small; Scott J. Goetz (Ecosystems, 2004)

Response of terrestrial carbon uptake to climate interannual variability in China - MINGKUI CAO; STEPHEN D. PRINCE; KERANG LI; BO TAO; JENNIFER SMALL; XUEMEI SHAO (Global Change Biology, 2003)
The interest in national terrestrial ecosystem carbon budgets has been increasing because the Kyoto Protocol has included some terrestrial carbon sinks in a legally binding framework for controlling greenhouse gases emissions. Accurate quantification of the terrestrial carbon sink must account the interannual variations associated with climate variability and change. This study used a process‐based biogeochemical model and a remote sensing‐based production efficiency model to estimate the variations in net primary production (NPP), soil heterotrophic respiration (HR), and net ecosystem production (NEP) caused by climate variability and atmospheric CO 2 increases in China during the period 1981–2000. The results show that China's terrestrial NPP varied between 2.86 and 3.37 Gt C yr −1 with a growth rate of 0.32% year −1 and HR varied between 2.89 and 3.21 Gt C yr −1 with a growth rate of 0.40% year −1 in the period 1981–1998. Whereas the increases in HR were related mainly to warming, the increases in NPP were attributed to increases in precipitation and atmospheric CO 2 . Net ecosystem production (NEP) varied between −0.32 and 0.25 Gt C yr −1 with a mean value of 0.07 Gt C yr −1 , leading to carbon accumulation of 0.79 Gt in vegetation and 0.43 Gt in soils during the period. To the interannual variations in NEP changes in NPP contributed more than HR in arid northern China but less in moist southern China. NEP had no a statistically significant trend, but the mean annual NEP for the 1990s was lower than for the 1980s as the increases in NEP in southern China were offset by the decreases in northern China. These estimates indicate that China's terrestrial ecosystems were taking up carbon but the capacity was undermined by the ongoing climate change. The estimated NEP related to climate variation and atmospheric CO 2 increases may account for from 40 to 80% to the total terrestrial carbon sink in China.